2015
DOI: 10.1080/19415257.2014.986813
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating self-study of teacher education practices: toward a pedagogy of teacher educator professional development

Abstract: This article reports on a two-year study of a self-study research group facilitation. The research group was designed as a professional development project in which six experienced teacher educators investigated their practices using a selfstudy approach. The pedagogical rationale of the facilitation was based on four broadly shared theoretical principles on how teacher educators can effectively work on their professional development. These theoretical principles were translated in a series of propositions ('i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 36 publications
1
57
0
3
Order By: Relevance
“…Otra limitante en la estrategia utilizada, pudo ser la probable excesiva confianza por parte de los investigadores/ facilitadores respecto a la potencialidad de trabajar con los docentes sobre los contenidos de sus propias teorías subjetivas, recogidos en la etapa "antes"; podemos hipotetizar que exponerles a los docentes sus propias creencias, podría haber generado resistencia en ellos e inhibirse así actitudinalmente ante esta intervención. Equilibrar la generación de confianza en los facilitadores, sin sacrificar el rol que tienen de confrontar a los participantes y generar una cierta "incomodidad productiva" o generadora de cambio, es un desafío reconocido (Vanassche & Kelchtermans, 2015).…”
Section: Discussionunclassified
“…Otra limitante en la estrategia utilizada, pudo ser la probable excesiva confianza por parte de los investigadores/ facilitadores respecto a la potencialidad de trabajar con los docentes sobre los contenidos de sus propias teorías subjetivas, recogidos en la etapa "antes"; podemos hipotetizar que exponerles a los docentes sus propias creencias, podría haber generado resistencia en ellos e inhibirse así actitudinalmente ante esta intervención. Equilibrar la generación de confianza en los facilitadores, sin sacrificar el rol que tienen de confrontar a los participantes y generar una cierta "incomodidad productiva" o generadora de cambio, es un desafío reconocido (Vanassche & Kelchtermans, 2015).…”
Section: Discussionunclassified
“…Vanassche and Kelchterman's (2016) work revealed how, at times, the participants in their research fostered supportive collegial relations with one another, but how these relations can inhibit more substantive and productive professional development by limiting more challenging and critical questioning of participants' normative perspectives on practice. However, and unlike the Vanassche and Kelchtermans (2016) research, the facilitators in the research reported here (in the form of the reading coach and the HOC) were not external persons, but members of the group (although their status as reading coach and HOC, as opposed to 'regular' (full-time classroom) teachers, did confer something of an 'outsider' status of sorts, and upon which they could draw to foster more critical inquiry on the part of other members of the group). This is not to underplay the difficulties associated with such work.…”
Section: Findings: Teachers' Learning In Actionmentioning
confidence: 99%
“…In this sense, the processes at play were indicative of broader normalizing responses that construe such problems as 'deserving of sustained attention' (Little and Horn, 2007: 88). This work of normalizing responses towards teaching as an object of collective attention can be challenging, as evidenced in Vanassche and Kelchtermans (2016) research into the facilitation of self-study of teacher education practices. Vanassche and Kelchterman's (2016) work revealed how, at times, the participants in their research fostered supportive collegial relations with one another, but how these relations can inhibit more substantive and productive professional development by limiting more challenging and critical questioning of participants' normative perspectives on practice.…”
Section: Findings: Teachers' Learning In Actionmentioning
confidence: 99%
See 2 more Smart Citations